Farmers’ video testimonials to scale out climate-smart agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
CCAFS has documented farmers’ testimonials on climate-smart agriculture through several short ﬁlms. The ﬁlms form an important repository of the various interventions being used in Climate-Smart Villages in Bihar and Haryana. Apart from capturing ﬁeld experiences, they also serve as valuable extension material in scaling out climate-smart agriculture practices.